CONSUMPTION OF ULTRA-PROCESSED PRODUCTS AND COFFEE AMONG UNIVERSITY PROFESSORS: AN ANALYSIS BY AREA OF ACTIVITY - Silva Barros, Acacio; Helena de Souza Queiroz, Camila (Health and Society, 2025)
Contemporary diets have been marked by the increased consumption of ultra-processed foods, rich in sugars, fats and additives, often associated with chronic non-communicable diseases (NCDs). Coffee, one of the most consumed beverages worldwide, has been studied for its stimulating effects and potential health benefits. In the university environment, professors face long working hours and high levels of stress, factors that influence their food choices. However, there is a gap in the literature on the consumption of ultra-processed foods and coffee among university professors, considering their area of ​​activity. This study aims to analyze the consumption of these products among professors from different areas of knowledge, understanding structural and cultural factors that influence such choices and proposing strategies to promote healthy eating. The research, with a quantitative and cross-sectional approach, will use structured questionnaires for data collection, with a sample stratified between health sciences, humanities and exact sciences. Statistical analysis will be conducted through tests such as ANOVA and logistic regression. The results indicated that coffee consumption is high, varying between academic areas. Health and exact sciences professors consume 1 to 3 cups a day, while biology professors have a lower prevalence. As for ultra-processed foods, the frequency also varies, being lower in the biology area. The conclusions highlight the need for institutional strategies to encourage healthy eating habits, contributing to the quality of life and performance of professors in the university environment.